PULMONARYTUBERCULOSIS IN RIO DE JANEIRO: A TIME FRAME - Santos de Almeida, Thiago Tadeu; Boçon Junior , Francisco; Pereira de Carvalho , Igor; Ferreira Cortez, Igor; Machado Martins , Higno Rafael; de Almeida Fonseca , Marcilene Maria; Sampaio da Fonseca , Walter Luiz Moraes (Cadernos ESP, 2022)
To correlate socioeconomic and epidemiological data from confirmed cases of pulmonary tuberculosis with the aggravating factors. Descriptive retrospective study of notified cases of pulmonary Tuberculosis registered in the Notification System, from January 2014 to December 2019, and correlated to data collected from the 2010 census, Atlas Brasiland the Instituto Trata Brasil. The analysis of the epidemiological situation in the city of Rio de Janeiro allowed us to observe a multifactorial correlation for the high rates of notification of pulmonary Tuberculosis. Therefore, investing to improve only one factor in this complex relationship will not have significant results. In other words, for the National Tuberculosis Control Program in Primary Care to be able to correctly treat 100% of diagnosed tuberculosis in the city of Rio de Janeiro.